The prevalence and socio-economic determinants of HIV among teenagers aged 15-18 years who were participating in a mobile testing population based survey in 2013-2014 in Zambia - Pascalina Chanda-Kapata; Eveline Klinkenberg; Nicole Maddox; William Ngosa; Nathan Kapata (BMC, 2016)
Abstract Background The objective of the study was to estimate the prevalence of HIV among teenagers in Zambia and determine whether age, sex, setting, educational level, marital and socioeconomic status were associated with being HIV positive. Methods A cross sectional population based survey of the prevalence of HIV among teenagers aged 15-18 years old who were also participants in a national Tuberculosis (TB) prevalence survey. Consenting teenagers were counselled and tested for HIV. The HIV prevalence was estimated using a logistic regression model. Associations of social demographic characteristics with HIV were determined using univariate and multivariate. Results The study involved 6,395 teenagers aged 15-18 years where 2,532 declined HIV testing, 44 tested positive and 3,806 tested negative. The HIV prevalence was estimated to be 1.1 % (95 % CI 0.71-1.60); in females the HIV prevalence was 1.6 % (95 % CI 0.99-2.20) whereas in males it was 0.58 % (95 % CI 0.10-1.10). The prevalence of HIV was twice as high among the urban (1.90 %; 95 % CI 0.99-2.90) than the rural teenagers (0.89 %; 95 % CI 0.46-1.30), and being divorced or widowed was associated with higher risk of HIV regardless of residence. The risk of HIV was lower among students or those who were in school compared to those who were unemployed and not in school. Conclusion HIV prevalence among teenagers was lower than the overall national level prevalence. The patterns of HIV risk among the young population will require further monitoring in order to identify appropriate tools for intervention.